Chronic Obstructive Pulmonary Disease (AYUSHDHARA, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable and treatable lung disease. It is characterized by chronic respiratory symptoms and airflow limitation due to abnormalities of the airways caused by continuous exposure to noxious particles or gases. COPD occupies the third position for the cause of death worldwide. The major risk factor for the development of COPD is tobacco smoking. The inhalation of toxic particles, biomass exposure and outdoor air pollution along with other host factors including abnormal lung development and accelerated lung aging can also contribute. Spirometry characterized by non-fully reversible airflow limitation i.e., FEV1/FVC < 0.7 post bronchodilation, confirms the diagnosis of COPD. The major goals of management are to reduce risk factors, manage stable COPD, prevent and treat acute exacerbations, and manage associated illnesses. The conservative management comprising of antibiotics, inhaled corticosteroids, mucolytics etc. offer promising results in this condition. But tachycardia, glossitis, glaucoma, nausea are some of the common adverse reactions noticed on chronic use of these group of drugs. The contemporary health scenario demands more contribution in this regard from the indigenous system of medicine. In Āyurvedic view, COPD can be considered under the spectrum of Prāṇavaha srotodushti vikaras. The clinical features and etiology mentioned for diseases mentioned in Ayurveda such as Kāsa, Tamaka śvāsa, Rajayakshma etc has similarity with that of COPD. Though COPD cannot be correlated to any single condition of Prāṇavaha sroto duṣti, Tamaka śvāsa can be considered as includes most of the clinical features including cough. When the etiological factors favour, the vitiated and aggravated Kapha dosha blocks the channels of Prāna and Udāna vāta causing the onset and symptoms of the disease.